Paradigmas estratégicos de gestão de manufatura nos pólos de Franca, Birigui e Jaú: análise por meio de um survey. - Bachega, Stella Jacyszyn (2006)
This research presents the application of the Strategic Manufacturing Management Paradigm (SMMP) identification method and the most appropriate SMMP for an organization in the three main footwear areas of the state of São Paulo: Franca, Birigui and Jaú. This method was developed by Godinho Filho e Fernandes (2006a). The research procedure used was survey. Thirty companies were selected using random probabilistic sampling, where 10 of them were interviewed in each studied area. Only 29 companies that composed the sample participated in the research. Based on the identification of the used SMMPs, it was verified that most of the companies didn t have strategic focus, which was elucidated by cases of inconsistency among ends and means. The SMMPs identified in some companies were: Responsive manufacturing and Mass customization. During the identification of the ideal SMMPs, it was observed that most of the companies focused non-coherent objectives due to the turbulence of the market in which they are inserted into. Amongst the SMMPs considered appropriate to some companies, the following could be identified: Responsive Manufacturing/ Mass Customization and Mass Customization/Agile Manufaturing. This dissertation presents contributions for the Production Management literature, by means of the identification of the possible types of strategic integration in an organization, as for the Brazilian shoe factoring market, supplying relevant information for a field that is in crisis, besides motivating new researches on the researched theme.